Unified secure access service edge (SASE): transforming security for hybrid workforce and multi-cloud environments - Attarbashi, Zainab; Basri, Atikah Balqis; Senan, Shayma (IIUM Press, 2025)
Organizations increasingly adopt hybrid cloud infrastructures and hybrid workforce models, creating a demand for secure and seamless networking solutions. Unified Secure Access Service Edge (SASE) is an integrated architecture that combines wide-area networking (WAN) functionality with advanced network security, offering a unified solution to address these challenges. This article explores the key components of Unified SASE and their effectiveness in handling the complexities of cloud infrastructure adoption and hybrid work environment integration. By embedding security capabilities into a cloud-based framework, Unified SASE ensures rapid responses to evolving threats and facilitates consistent security policies across on-premise data centres and multi-cloud environments. This article emphasizes the importance of adhering to industry standards in the development and deployment of Unified SASE, particularly regarding compatibility and interoperability. Ultimately, Unified SASE addresses the challenges of cloud environments and hybrid workforce models by integrating network security with access services, providing enterprises with a robust framework for secure, efficient, and scalable operations